2016
DOI: 10.1002/jor.23270
|View full text |Cite
|
Sign up to set email alerts
|

Decreased osteogenesis in mesenchymal stem cells derived from the aged mouse is associated with enhanced NF‐κB activity

Abstract: Aging is associated with significant bone loss and delayed fracture healing. NF-κB activation is highly correlated with inflammatory-associated bone diseases including infection, wear particle exposure, and chronic inflammation during natural aging processes. The critical roles of NF-κB in both the pro-inflammatory response and osteoclast-mediated bone resorption have been well defined. However, the biological effects of NF-κB activation in mesenchymal stem cell (MSC)-mediated bone formation remain largely unk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 20 publications
(67 reference statements)
0
62
0
Order By: Relevance
“…2b). To clarify whether IL-4 can affect the secretion profiles in MSC NF-κBRE IL4 exposed to LPS in an autocrine manner, MSCs were infected with NF-κB luciferase reporter lentivirus as previously described [18]. The results showed that the NF-κB activation patterns induced by intermittent (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2b). To clarify whether IL-4 can affect the secretion profiles in MSC NF-κBRE IL4 exposed to LPS in an autocrine manner, MSCs were infected with NF-κB luciferase reporter lentivirus as previously described [18]. The results showed that the NF-κB activation patterns induced by intermittent (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The lentiviral NF-κB luciferase reporter vector (pCDH-NF-κB-luc2p-copEGFP) was generated previously[18]. Murine MSCs were infected by the reporter viral vectors as described in the “preparation and infection of lentiviral vector” section.…”
Section: Methodsmentioning
confidence: 99%
“…In one study using a murine model, NF-κB activation (increased phosphorylation of RelA) has been reported in the trabecular bone in natural aging mice (Yu et al, 2014). Furthermore, increased NF-κB activity was found in the MSCs isolated from aged mice (15 months) compared with younger mice (Lin, Gibon, et al, 2016). Inhibition of the NF-κB pathway partially rescued the reduction of osteogenesis in aged MSCs.…”
Section: Inflammation and Bone Disordersmentioning
confidence: 96%
“…Recognition of wear particles or DAMPs adhering to the particles via TLR2 and TLR4 induces the secretion of proinflammatory cytokines in the NF-κB-dependent pathway (Pearl et al, 2011). The proinflammatory cytokines including TNF-α and IL-1β further activate NF-κB in macrophages as a positive regulatory loop during the chronic inflammation, leading to OC activation, and osteolytic processes (Lin, Pajarinen, et al, 2016; Lin, Tamaki, et al, 2014). Inhibition of NF-κB activity suppresses PMMA and UHMWPE wear particle induced OC activation in vitro and in vivo, suggesting the therapeutic potential of targeting NF-κB pathway in the particle disease (Clohisy, Hirayama, Frazier, Han, & Abu-Amer, 2004; Lin, Pajarinen, et al, 2016).…”
Section: Inflammation and Bone Disordersmentioning
confidence: 99%
“…RANKL and its receptor RANK expressed on osteoclast precursors is essential for osteoclast differentiation and activation . RANKL is expressed in differentiated osteoblast‐lineage cells and has also been reported to be expressed in MSCs isolated from aged mice . MSCs regulate osteoclast formation also by secreting osteoprotegerin (OPG), the RANKL decoy receptor.…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%